The Long Term Outcome of Type-1 Diabetes Mellitus in Children. - Putri Arsya Saragih; Suparto Suparto; Suryadi Susanto (Fakultas Kedokteran dan Ilmu Kesehatan Ukrida, 2023)
Type-1 diabetes mellitus (DM) is a systemic disorder resulting from impaired glucose metabolism characterized by chronic hyperglycemia due to pancreatic β-cell destruction due to both autoimmune and idiopathic processes, resulting in reduced insulin production and even stopping. Over time, long-term complications arise.the objective of this literature review is to knowing long-term outcomes in the form of nephropathy, neuropathy, retinopathy and short-term complications in the form of hypoglycemia and ketoacidosis. Based on searches, PubMed, Google Scholar and Proquest found 76 literature with the keywords “(“Diabetes Mellitus Type 1”, “Long Term Outcome DM Type 1 pediatric”, “Long Term Management DM Type 1 pediatric”.)”. After the screening stage was carried out based on inclusion criteria and fulfilling the writing criteria so that only 7 literature was found and could be used for literature review.The development of microalbuminuria in children is greater than in adults with an odds ratio of 2.6 so that eventually the formation of nephropathy becomes an odds ratio of 3.8 and retinopathy odds ratio of 2.1. long-standing type 1 diabetes has resulted in psychosocial disturbances, most of which are internalization disorders and mental-emotional disorders. Long-term outcomes of type 1 diabetics in the form of incidents of neuropathy, nephropathy, proliferative retinopathy and emotional mental disorders